Sphingolipids Are Dual Specific Drug Targets for the Management of Pulmonary Infections: Perspective - Sharma, Lalita; Prakash, Hridayesh (Frontiers in Immunology, 2017)
Sphingolipids are the major constituent of the mucus secreted by the cells of epithelial linings of lungs where they maintain the barrier functions and prevent microbial invasion. Sphingolipids are inter-convertible and their primary and secondary metabolites have both structural as well as functional role. Out of several sphingolipid metabolites, S1P and ceramide are central molecules and decisive for sphingolipid signalling. These are produced by enzymatic activity of sphingosine kinase - 1 (SK-1) upon the challenge with either biological or physiological stresses. Sphingosine-1 phosphate and ceramide rheostat is important for the progression of various pathologies which are manifested by inflammatory cascade. S1P is a well-established secondary messanger and associated with various neuronal, metabolic and inflammatory diseases other than respiratory infections such as Chlamydia pneumoniae, Streptococcus pneumoniae and Mycobacterium tuberculosis. These pathogens are known to exploit sphingolipid metabolism for their opportunistic survival. Decreased sphingosine kinase activity/ S1P content in the lung and peripheral blood of tuberculosis patients, clearly indicated a dysregulation of sphingolipid metabolism during infection and suggest that sphingolipid metabolism is important for management of infection by the host. Our previous study has demonstrated that gain of SK-1 activity is important for the maturation of phagolysosomal compartment, innate activation of macrophages and subsequent control of mycobacterial replication/ growth in macrophages. Furthermore, S1P mediated amelioration of lung pathology and disease severity in TB patients is believed to be mediated by the selective activation or rearrangement of various S1P receptors particulary S1PR2, which has been effective in controlling respiratory fungal pathogens. Therefore such specificity of S1P-S1PR would be paramount for triggering inflammatory events, subsequent activation and fostering bactericidal potential in macrophages for the control of TB. In this review we have discussed and emphasized that Sphingolipids may represent effective novel, yet dual specific drug targets for controlling pulmonary infections